All aboard: users' experiences of adapted paddling programs. Issue 20 (25th September 2021) - Merrick, Darien; Hillman, Kyle; Wilson, Alice; Labbé, Delphine; Thompson, Alex; Mortenson, W. Ben
Abstract: Purpose: Research has yet to examine the experiences of paddle boarders, or of kayakers with disabilities other than spinal cord injuries. The goal of this study was to explore the experiences of kayakers and paddle boarders in two adaptive paddling programs. Method: Participants were children and adults requiring physical, cognitive, and/or psychosocial supports. Using an ethnographic approach, participant observations ( n  = 24) and semi-structured interviews ( n  = 11) were completed. Data were analyzed thematically. Result: We identified three main themes. "Different Strokes" described the personal meaning participants ascribed to aspects of paddling, including valuing fun, exercise and relaxation. "Turning the Tide" illustrated the process of becoming a paddler, from doubting capacity to feeling competent. "Headwinds" explored paddlers' interactions with the broader social, institutional, and economic environments, such as inadequate funding and program aversion to risk. Conclusions: Programs offering a variety of adaptive paddle boarding and kayaking configurations enable paddlers to make valued choices about their participation. In addition to providing equipment and support to meet paddlers' functional abilities, program developers and clinicians should also consider individual preferences for exercise, socialization, risk taking, self-presentation of disability, and independence. IMPLICATIONS FOR REHABILITATION: People living with physical, cognitive, and/or psychosocial impairments perceive kayaking and paddle boarding as meaningful activities offering opportunities to exercise, have fun, achieve goals, socialize, and/or relax on the water. Kayakers and paddle boarders value equipment options that meet their physical and disability-disclosure preferences. Despite the existence of adaptive paddling programs, participation may be restricted by program availability, risk management policies, and leisure funding.